Comparative Histology of the Skin Between Sumba Ongole Cattle (Bos indicus) and Bali Cattle (Bos sondaicus) - Amalo, Filphin Adolfin; Maha, Inggrid Trinidad; Toan, Vilomena Kusi; Nitbani, Heny; Gaina, Cynthia D. (Hasanuddin University, 2024)
This study aims to determine the histological structure of the skin and the distribution of sweat glands in Sumba ongole and Bali cattle. Skin samples from the nuchalis and fascia superfialis dorsalis regions were collected from six Sumba ongole cattle slaughtered at the East Sumba slaughterhouse and six Bali cattle slaughtered at the Oeba Kupang slaughterhouse. The samples were fixed in 10% formalin, histological preparations were made, and HE staining was performed. The results showed that the histological structure of the skin of Sumba ongole and Bali cattle was similar to other mammals, with three layers: epidermis, dermis, and hypodermis. The mean number of sweat glands in the nuchalis region of Sumba ongole cattle (13.33 ± 5.13/mm2) was higher than that of Bali cattle, while the fascia superfialis dorsalis region of Bali cattle had a higher average number of sweat glands (13.66 ± 4.16/mm2) than in Sumba ongole cattle